Dairy intake and the risk of pancreatic cancer: the Japan Collaborative Cohort Study (JACC Study) and meta-analysis of prospective cohort studies. Issue 6 (28th September 2022) - Arafa, Ahmed; Eshak, Ehab Salah; Dong, Jia-Yi; Shirai, Kokoro; Muraki, Isao; Iso, Hiroyasu; Tamakoshi, Akiko
Abstract: Dairy product intake was suggested to reduce the risk of gastrointestinal cancers. This study investigated the association between dairy product intake and the risk of pancreatic cancer (PAC) using a prospective cohort study and meta-analysis of prospective cohort studies. First, we included 59 774 people aged 40–79 years from the Japan Collaborative Cohort Study (JACC Study). The Cox regression was used to compute the hazard ratios (HR) and 95 % CI of incident PAC for individuals who reported the highest intakes of milk, cheese and yogurt compared with not consuming the corresponding dairy products. Then, we combined our results with those from other four prospective cohort studies that were eligible after searching several databases, in a meta-analysis, using the fixed-effects model before evaluating publication bias and heterogeneity across studies. In the JACC Study, the highest v . no intakes of milk, cheese and yogurt were not associated with the reduced risk of PAC after a median follow-up of 13·4 years: HR (95 % CI) = 0·93 (0·64, 1·33), 0·91 (0·51, 1·62) and 0·68 (0·38, 1·21), respectively. The results did not significantly change in the meta-analysis: 0·95 (0·82, 1·11) for milk, 1·16 (0·87, 1·55) for cheese and 0·91 (0·79, 1·05) for yogurt. The meta-analysis showed no signs of publication bias or heterogeneity across studies. To conclude, consumption of milk, cheese and yogurt was not associated with the risk of PAC either in the JACC Study or the meta-analysis.